An Assessment of the Development of a Mobile Agricultural Biogas Plant in the Context of a Cogeneration System - Zbigniew Jarosz; Magdalena Kapłan; Kamila Klimek; Barbara Dybek; Marcin Herkowiak; Grzegorz Wałowski (Applied Sciences, 2023)
This article presents examples of cogeneration systems, which are standard equipment for biogas installations, based on the production of heat and electricity. It has been shown that in the case of microgeneration, ease of servicing and low installation costs are crucial. Characteristic aspects of developing concepts for mobile installations (small scale) that produce biogas, often with a simple container structure that is ready to be located in the economic infrastructure of the agricultural industry, were indicated. Recommendations for the operation of micro-biogas models are presented, which have the greatest impact on the advisability of using agricultural waste for energy purposes. A characteristic farm was selected, which has a substrate necessary for the process of methane fermentation of slurry from pig farming. The cogenerator, which constitutes a potential energy demand from the point of view of Polish agriculture in the context of renewable energy production, was analyzed. The research goal was to adapt the cogenerator to the conditions existing on a farm, which should meet the technical and technological expectations for the process of managing the produced methane with a value of 80% in agricultural biogas. The assessment of the impact of the amount of biogas on the level of CO, NO, NO2 and PM emissions was carried out at a constant engine speed for various load levels; the percentage of biogas was changed from 40 to approximately 70–80%, i.e., until significant knocking combustion was detected in the tested engines. As a result, the existing control and control system for the operation of the cogeneration unit prevents the most effective mode of operation of the research installation as a prosumer micro-installation. When the AG20P biogas unit operated in parallel with the grid with an active power of up to 11.7 kW, the electricity produced by the unit met the adopted assumptions and requirements. What is new in this article is the use of a cogeneration unit that has been adapted to its functionality, taking into account the assessment of the prospects for optimizing the cogeneration system in the context of the use of renewable energy sources as agricultural biogas. The best method was to attempt to determine the operating conditions of the cogenerator to develop the optimization of a biogas cogeneration unit producing electricity and heat in a micro-installation for the needs of an individual farm.